Data structures, algorithms, and applications in Java - Sahni, Sartaj (Boston : McGraw-Hill, 2000)
"Data Structures, Algorithms, and Applications in Java provides comprehensive coverage of fundamental data structures, making it ideal for use in a CS2 course. Sahni has made this text the most student friendly of all his text-books by using a gentle introduction, providing intuitive discussions, and including real-world applications."--BOOK JACKET.
Pt. I. Preliminaries. Ch. 1. Java Review. Ch. 2. Performance Analysis of Programs. Ch. 3. Asymptotic Notation. Ch. 4. Performance Measurement of Programs -- Pt. II. Data Structures. Ch. 5. Linear Lists - Array Representation. Ch. 6. Linear Lists - Linked Representation. Ch. 7. Linear Lists - Simulated Pointers. Ch. 8. Arrays and Matrices. Ch. 9. Stacks. Ch. 10. Queues. Ch. 11. Skip Lists and Hashing. Ch. 12. Binary and Other Trees. Ch. 13. Priority Queues. Ch. 14. Tournament Trees. Ch. 15. Binary Search Trees. Ch. 16. Balanced Search Trees. Ch. 17. Graphs -- Pt. III. Algorithm-Design Methods. Ch. 18. The Greedy Method. Ch. 19. Divide and Conquer. Ch. 20. Dynamic Programming. Ch. 21. Backtracking (On the Web). Ch. 22. Branch and Bound (On the Web).
Includes bibliographical references and index.
Keywords: Java (Computer program language); Data structures (Computer science); Computer algorithms; Application software -- Development